Effects of variation theory-based strategy on form two students' algebraic achievement and motivation - Ting, Jing Jing (2016)
This study investigated the effects of utilizing Variation Theory-Based Strategy (VTBS) on students’ algebraic achievement and their motivation in learning algebra. Examination on difficulties in learning Form Two algebra faced by both experimental and control groups in urban and rural were also conducted. The study used quasi-experimental non-equivalent control group research design. It involved 120 Form Two students in four intact classes (two classes were from an urban school, another two classes from a rural school) in Sarawak, Malaysia. The first group of students from each school learnt algebra through VTBS while the second group of students in each school learnt algebra through Conventional Teaching Strategy (CTS). A 24-item Algebra Test (Chow, 2011) and a 36-item Instructional Material Motivation Survey (Keller, 2010) questionnaire were administered to measure students’ algebraic achievement and motivation of learning and its four subscales; attention, relevance, confidence, and satisfaction. ANCOVA analysis showed that that VTBS had significant effect on students’ algebraic achievement from both locations with urban students had significant better performance than their counterparts in rural school (p<0.05). Two-way ANOVA showed there were significant interaction effects in terms of instructional strategy and school location on students’ overall motivation of learning and its four subscales: attention, relevance, confidence, and satisfaction (p<0.05). There were evidences that VTBS had significant effect on rural VTBS students’ overall motivation of learning in all the four subscales but it was not so for urban VTBS students’ motivation. The rural students in experimental group were more motivated in the environment of VTBS which had captured the interest of students (attention), met their personal needs (relevance), assisted them to have believe and control success (confidence), and allowed them to have good experiences (satisfaction). The result of the study showed that the primary predicament in learning algebra faced by VTBS and CTS groups was use of appropriate algebraic expression in making relationship. Both groups of students also encountered problem in use of appropriate rules to solve problems. The result of the study also showed that rural students did not perform well in understanding of variables in algebra. Inadequate understanding of algebraic symbols and the used of its properties when it was used in an equation was also a major problem that hindered the students solving equations correctly. The result of the study confirmed the effectiveness of VTBS in learning algebra. The developed learning modules had incorporated variation theory into algebra learning activities and tasks. The result also demonstrated the potential of VTBS as useful learning strategy particularly among students in rural Malaysian schools.